Estimating the impact of shocks to bank capital in the euro area - Derrick Kanngiesser; Reiner Martin; Laurent Maurin; Diego Moccero (European Central Bank (ECB), 2017)
We contribute to the empirical literature on the impact of shocks to bank capital in the euro area by estimating a Bayesian VAR model identified with sign restrictions. The variables included in the VAR are those typically used in monetary policy analysis, extended to include aggregate banking sector variables. We estimate two shocks affecting the euro area economy, namely a demand shock and a shock to bank capital. The main findings of the paper are as follows: i) Impulse-response analysis shows that in response to a shock to bank capital, banks boost capital ratios by reducing their relative exposure to riskier assets and by adjusting lending to a larger extent than they increase the level of capital and reserves per se; ii) Historical shock decomposition analysis shows that bank capital shocks have contributed to increasing capital ratios since the crisis, impairing bank lending growth and contributing to widen bank lending spreads; and iii) counterfactual analysis shows that higher capital ratios pre-crisis would have helped dampening the euro area credit and business cycle. This suggests that going forward the use of capital-based macroprudential policy instruments may be helpful to avoid a repetition of the events seen since the start of the global financial crisis.
Keywords: G21; C32; C11; 330; Euro area; Bank Balance Sheet Adjustment; Capital Ratio; Bayesian VAR; Macroprudential Policy; Sign Restrictions